Cost Components Illness Analysis of Type 2 Diabetes Mellitus by Class of Care - Firman, Firman; Lestari, Kartika (GLOBAL HEALTH SCIENCE GROUP, 2023)
The cost of treating DM disease is one of the portraits of chronic diseases that require significant medical expenses The burden of treatment costs for DM patients will be more expensive if complications occur because it has an impact on the need for drugs and therapies that last a lifetime. This study aimed to identify the cost components of inpatient treatment of Type II DM patients with Peripheral Circulation complication according to treatment class at PKU Muhammadiyah Bantul Hospital. Qualitative research design with case study design. The sampling technique was carried out by purposive sampling and the data collected were 50 patients. The main data sources were obtained from Medical Records and Financial Administration data from Medical Records, Pusjamkes, and Finance units The cost components analyzed included consultation fees, action fees, treatment fees, support and accommodation with comparisons between inpatient classes. This study showed that the largest cost treatment component of DM patients was Very Important Person (VIP) patients with an average doctor’s consultation fee per patient (Rp.660.500), accommodation costs (Rp2.006.000), and action costs (Rp.4.415.000). Meanwhile, the largest average supporting costs (Rp.3.300.844) and treatment (Rp527.695) were found in class II patients. This indicates that the tendency of the supporting cost components is very dominant because it is influenced by the specifications of the services needed such as laboratory examination costs, and radiology costs which are influenced by blood transfusion factors, hemoglobin and albumin, and the types of antibiotics needed during treatment. Hospital managers can carry out quality control and especially control the costs of drugs and medical consumables by complying with the provisions of patient treatment and care.